But Was it Just? : Reflections on the Morality of the Persian Gulf War - Elshtain, Jean Bethke, 1941-2013 [et al.]; Edited By David E. DeCosse (Rawalpindi Army Education Press, 2001)
President George Bush said yes; some bishops said no; even Doonesbury touched on the question. But what does it mean, in any case, to say that a war is just? What are the yardsticks of justice that support President Bush's claim that it was just to reverse Iraq's invasion of Kuwait? And how does one evaluate the justness of stopping the war when the allies did? And what of our fierce bombing of the fleeing Iraqi
Include Appendix
Keywords: Persian Gulf War, 1991 -- Moral and ethical aspects. -- Persian Gulf War, 1991 -- Religious aspects. -- Just War Doctrine